2014
DOI: 10.1080/1070289x.2014.939185
|View full text |Cite
|
Sign up to set email alerts
|

Becoming independent through au pair migration: self-making and social re-positioning among young Filipinas in Denmark

Abstract: Over the past decade, growing numbers of young Filipinas have entered Denmark on the au pair scheme. While its official aim is to broaden the cultural horizons of youth, researchers generally view Filipina au pairing as a form of labour migration using au pairs as inexpensive domestic workers. This article argues that, despite this critique, au pairing does play an important formative role for young Filipinas because it opens up for experiences abroad that enable them to be recognised as independent adults in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Hence, from a Philippine perspective, the au pairs' sacrifices entail a strong sense of agency -their travel abroad is a conscious act enabling them to help those at home -and this seemingly selfless act of migration actually speaks to ideas of heroism connected to being an overseas Filipino. Indeed, to get through the trials they face abroad provides a path to social recognition and status in the au pairs' home communities (see Dalgas, 2015).…”
Section: Facebook Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, from a Philippine perspective, the au pairs' sacrifices entail a strong sense of agency -their travel abroad is a conscious act enabling them to help those at home -and this seemingly selfless act of migration actually speaks to ideas of heroism connected to being an overseas Filipino. Indeed, to get through the trials they face abroad provides a path to social recognition and status in the au pairs' home communities (see Dalgas, 2015).…”
Section: Facebook Discussionmentioning
confidence: 99%
“…As Olwig and Valentin (2015) argue, by primarily focusing on the exploitive conditions that migrants are subjected to, researchers can come to reinforce a negative image of the migrants as a 'racialized labor force performing the dirty, badly paid work that the local population is not willing to do' (Olwig and Valentin 2014:254). There is, however, a new wave within au pair research that aims at exploring other aspects of au pair migration than that which can be exhibited by employing a labour framework (see, for example, Búrikova & Miller 2010, Dalgas 2015, Rohde 2012. Tkach 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the Russian au pairs in Germany, studied by the sociologist Caterina Rohde-Abuba (Rohde 2012), the Filipino au pairs explained that they have gone abroad in order to travel and see the world, to become more independent and to release themselves from parental control (Dalgas 2015). Au pair placement is one of the few ways in which they can enter Denmark, being non-EU citizens with limited financial means.…”
Section: Filipino Au Pairsmentioning
confidence: 99%
“…However, as the anthropologist Pauline Gardiner Barber observed, even though Filipino migrants employed as domestic workers might experience disempowering conditions, they do not necessarily perceive themselves as disempowered (Barber 2002: 46). Rather, as several studies have shown, Filipino migrants can engage in ambivalent class processes in both the destination society and the society of origin (see Barber 2002;Bikova 2015;Dalgas 2015;Gibson et al 2001;Parreñas 2001).…”
Section: A Network-oriented Approach To Exploring Au Pair Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation